(untitled) (Journal of the College of Basic Education, 2023)
Evaluation of the activity concentration for natural terrestrial radiation in the Baghdad city has been achieved in this study, Gamma ray activities of radionuclides 226Ra,232Th and also the long-lived naturally occurring radionuclide 40K have been determined in soil samples for selected regions in Baghdad city by using gamma spectrometry( which contains High- purity Germanium Detector) with a efficiency of 40% and resolution 2 keV for Energy, 1.33Mev gamma ray photo peak of 60Co ,collection, preparations and tests of 25 soil samples were all done according to IAEA, The measuring time of all soil samples is 3600 seconds. It was found that, the soil specific activity ranges from(20.07 ± 1.86) to (41.10 ± 2.12) Bq/kg for (226Ra), (17.21 ±1.95) to (38.19 ±2.42 ) Bq/kg for (232Th) and (346.12± 8.19) to (613.97 ±10.00) Bq/kg for (40K) with mean values of (27.94 )Bq/kg,(25.24 )Bq/kg and (476.65) Bq/kg, respectively in AL KARKH side, while the soil specific activity ranges from (16.23 ± 1.25) to (35.52 ± 1.21) Bq/kg for (226Ra), (19.02 ± 2.8) to ( 30.57 ± 2.7) Bq/kg for (232Th) and (308.99 ± 9.92) to (593.74 ±11.90 ) Bq/kg for (40K) with mean values of (22.51) Bq/kg,(24.77) Bq/kg and (464.20) Bq/kg, respectively in AL RASAFAH side The average of radium equivalent activity (Raeq), the gamma absorbed dose rate (D) in air, the annual effective dose rate, and the rate of external hazard index have been calculated, the results were 95.84 (Bq/kg), 46.41 (nGy/h), 56.91x10-6 (Sv), 0.25 respectively in AL KARKH side, and 92.84 (Bq/kg),44.81 (nGy/h),54.96x10-6 (Sv), 0.24 in AL RASAFAH side respectively. Finally the results have been compared with the acceptable world average values (UNSCEAR, 2000).and According to results of this study we can regard the Baghdad city within the regions of normal background radiation which includes cosmic radiation arise in outer space and radionuclides in the earth’s crust.